Conflict Within the Union: Struggles Among Sydney Steel Workers, 1956-1972 - Crawley, Ron (Carleton University, 1995)
The thesis addresses the importance of intra-union struggles as a mediating factor in understanding the relationship between changes in union policies and strategies and the larger socio-economic environment. Examination of these intra-union struggles, the thesis argues, is necessary for a fuller understanding of the development of the union and the steel workers' ongoing contestation with the steel company. It examines the significance of intra-union conflict in the establishment of responsible" unionism and "industrial democracy" within the Canadian steel industry and in the context of international, national and local aspects of the union. During the period 1936-1972 the steel workers were organized within Local 1064 of the United Steel Workers of America which, according to the findings of the thesis, was marked by intra-union conflict almost from its inception. Conflict between an establishment-dominated leadership and its supporters and oppositional forces, which took different forms and displayed various degrees of influence within the local over time, was an integral part of the union's political life. Arguments drawn from Marxist theory and from the work of Michels are compared and evaluated in light of the historical record of the steel workers and their attempts to build an effective organization. The thesis demonstrates that oppositional activity within the union was crucial to understanding the development and direction of the union. The establishment and maintenance of "responsible" unionism and "industrial democracy" were mediated by intra-union struggles. The findings of the study offer support for both a Marxist and a Michelsian theory of change within such organizations.